Virtual Reality (VR) and Augmented Reality (AR): Immersive Experiences Transforming Entertainment, Education, and Training - Tongam E Panggabean (Education Studies and Teaching Journal (EDUTECH), 2024)
Virtual Reality (VR) and Augmented Reality (AR) technologies are increasingly being integrated into areas such as entertainment, education, and training, offering immersive and interactive experiences that can enhance learning and student engagement. This research aims to develop a more effective evaluation method in education and training using VR and AR technology compared to traditional methods. Using the PRISMA method, this research collects and analyzes articles from various reputable international databases. The research results show that VR and AR have great potential to improve student engagement and learning outcomes, but their successful implementation depends on the development of adaptive evaluation methods. This research provides practical guidance for the effective implementation of VR and AR in education and training and contributes to new literature in the field of educational technology.